The Mechanism of Munāsabah and Its Effect on Textual Cohesion in Surah Ṭāhā – An Applied Study - djokhdem, fatima (El Omda in Linguistics and Discourse Analysis, 2022)
Texte linguistiques resaches have established Rules and mécanismes for textural analysais, winch has a signifiant impact on textural cohésion, the se Arch for the concept of text and the critérié That définie it has remanie the obsession of Manny linguistes and resaches in the Field of textural linguistiques. The appropriâtes mécanisme, like Othe mécanismes and critérié, has receviez This attention of sud, resarci and analysais - especially amont Ancient Arab scholars-. Modernistes hard an important impact on the use of This mécanisme in textural analysais, we have chosent (Surat Taha) frome the Noble Quran to Under stand This mécanisme (i.e. the appropriâtes mécanisme) and know its impact on cohésion in keywords : Appropriât mechanism textural cohérence; texte; textural k